Development and analysis of a mechatronic system for in-process monitoring and compensation of straightness deviation in BTA deep hole drilling. (1st May 2022) - Gerken, Julian Frederic; Klages, Niklas; Biermann, Dirk; Denkena, Berend
Highlights: BTA deep hole drilling is often used at the end of the value chain for machining expensive components such as hydraulic cylinders, transmission shafts and aircraft landing legs. At this point, the component already has a high equivalent value, making high process reliability and adherence to tight manufacturing tolerances of enormous technical and economic importance. In addition to the classic bore requirements, such as low roundness and diameter deviation as well as good surface quality, the so-called straightness deviation is an important quality feature of deep bores. The straightness deviation often plays a decisive role for the functionality of the component, since it reflects the radial position error of the actual bore center axis relative to the ideal bore axis. Complete avoidance of straightness deviation is not possible due to the complex interactions between the influencing parameters. Because of this problem, a tooling system for in-process compensation of straightness deviation is highly needed. In this paper, a system for process-simultaneous compensation of the straightness deviation in BTA deep hole drilling was developed and researched. A newly constructed, manufactured and tested compensation unit, which is mounted between the drill head and the drill pipe, enables a targeted tilting of the drill head. For the first time, the developed measuring system offers the possibility to record the straightness deviation in amount and direction during the drilling process. Compared to the process without control and compensation unit, the progressive increase of the straightness deviation was significantly reduced. In order to achieve the required control quality of a maximum of 0.2 mm straightness deviation per meter drilling depth, the main influencing variables on the measurement system were identified and compensated. A system model of the process was developed to investigate the system. Based on test series, a control system was developed and applied to the process. After a drilling path of lB  = 1, 000 mm, an average straightness deviation reduction of approx. 40 % can be realized. By realizing and testing the demonstrator for controlled deep hole drilling, pre-competitive knowledge for the industrial feasibility of this technology was created. Under consideration of the outlined boundary conditions, this knowledge can be taken over directly by industrial users. The required investment and development costs for the implementation of the compensation system are reduced by applying the knowledge developed in this research project. Abstract: In BTA deep hole drilling straightness deviation of the bore is a very important quality criteria. The avoidance of straightness deviation is not possible due to the many influencing variables. Currently used methods for compensation require significant additional time, as they either require the interruption of the drilling process, or require an additional boring process. By using a newly developed, manufactured and tested compensation unit, which is mounted between the drill head and the drill pipe, a targeted tilting of the drill head and thus a targeted influencing of the straightness deviation in the running process is possible with the use of a radially adjustable control pad and an innovative actuator concept. The developed measuring system offers the possibility to record the straightness deviation during the drilling process. On the basis of experimental test series, a control system was developed and applied to the BTA deep drilling process. After a drilling path of 1, 000 mm, a maximum straightness deviation reduction of approx. 51 % can be realized. Compared to the process without control and compensation unit, the progressive increase of the straightness deviation was significantly reduced.